SNPkit: An Efficient Approach to Systematic Evaluation of Candidate Single Nucleotide Polymorphisms in Public Databases - K. Hao; T. Niu; C. Sangokoya; J. Li; X. Xu (BioTechniques)
There is widespread interest in devising genotyping methods for SNPs that are robust, inexpensive, and simple to perform. Although several high-throughput SNP genotyping technologies have been developed, including the oligonucleotide ligation assay, real-time PCR, and mass spectrometry, the issues of simplicity and cost-effectiveness have not been adequately addressed. Here we describe the application of a novel computer software package, SNPkit, which designs SNP genotyping assays based on a classical approach for discriminating alleles, restriction enzyme digestion. SNPkit can be used in genotyping assays for almost any SNPs including those that do not alter “natural” restriction sites. Using this method, 164 SNPs have been evaluated in DNA samples from 48 immortalized cell lines of randomly selected Chinese subjects. Sixty-two (37.8%) of the SNPs appeared to be common (frequencies of the minor alleles are ≥ 5%) and were subsequently applied to a larger population-based sample. Overall, by using SNPkit, we have been able to validate and genotype accurately a large fraction of publicly available SNPs without sophisticated instrumentation.